(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to find out the relationship between written expression and linguistic intelligence, according to gender, among sixth grade students in middle school / literary branch. To achieve this goal, the researchers chose a sample consisting of (240) male and female students in a random staging manner from the sixth grade students in the general directorates of education in the Baghdad governorate. To measure the editorial expression, the researchers adopted a topic for expression, and criteria for correcting it prepared by another researcher in a previous study. The researchers built a scale Linguistic intelligence according to scientific steps to build psychological and educational standards